ANALISIS PRAKTIK GADUH SAPI PADA MASYARAKAT DESA LEDOKTEMPURO KECAMATAN RANDUAGUNG KABUPATEN LUMAJANG BERDASARKAN FIQIH KONTEMPORER - Totok, Muhammad; Baehaqi, B; Sulistyowati, S (AL HUKMU: Journal of Islamic Law and Economics, 2024)
The purpose of this study was to find out the law of rowdy cows in the people of Ledoktempuro Village, Randuagung District, Lumajang Regency. The subjects of this study were the people of Ledoktempuro Village, Randuagung District, Lumajang Regency, East Java Province. Data collection techniques in this study used observation, interview, and documentation techniques. Then this study applied data analysis namely data reduction, data presentation and data verification. The results of this study indicate that the practice of rowdy cows is carried out from generation to generation as a proffesion to meet the needs of everyday life. In practice, the cow rowing agreement in this community is only verbal without any authentic or written evidence with an agreement on profit  sharing at the start. According to contemporary fiqh, the practice of cow rowing is included in the practice of mudharabah muqayyadah and may be carried out in accordance with Islamic law.